Classification and sources of extremely severe sandstorms mixed with haze pollution in Beijing. (1st April 2023) - Liu, Tianyi; Duan, Fengkui; Ma, Yongliang; Ma, Tao; Zhang, Qinqin; Xu, Yunzhi; Li, Fan; Huang, Tao; Kimoto, Takashi; Zhang, Qiang; He, Kebin
Abstract: Air quality has significantly improved in China; however, new challenges emerge when dust weather is combined with haze pollution during spring in northern China. On March 15, 2021, an extremely severe sandstorm occurred in Beijing, with hourly maximum PM10 and PM2.5 concentrations reaching 5267.7 μg m −3 and 963.9 μg m −3, respectively. Continuous sandstorm events usually lead to complicated pollution status in spring. Three pollution types were identified disregarding the time sequence throughout March. The secondary formation type was dominant, with high ratios of PM2.5 /PM10 (mean 74%) and PM1 /PM2.5 (mean 52%). This suggests that secondary transformations are the primary cause of heavy pollution, even during the dry seasons. Sandstorm type resulted in dramatic PM10 levels, with a noticeable decrease in PM2.5 /PM10 levels (27%), although PM2.5 levels remain high. The transitional pollution type was distinguished by an independent increase in PM10 levels, although PM2.5 and PM1 levels differed from the PM10 levels. Throughout March, the sulfur oxidation rate varied considerably, with high levels during most periods (mean 0.52). A strong correlation indicated that relative humidity was the primary variable promoting the formation of secondary sulfate. Sandstorms promote heterogeneous reactions by providing abundant reaction surfaces from mineral particles, therefore aggravating secondary pollution. The sandstorm air mass from the northwest passing through the sand sources of Mongolia carried not only crustal matter but also organic components, such as bioaerosols, resulting in a sharp increase in the organic carbon in PM2.5 . Graphical abstract: Image 1 Highlights: Three types of air pollution were identified: secondary formation, sandstorm and transitional pollution. Haze mixed with sandstorms caused more severe air pollution in Beijing. Air masses from Mongolia with high bioaerosol burden led to increased organic carbon concentrations.